Welfare Economic Aspects of Land Use Planning - Wilbert Grevers; Anne Van der Veen (European Regional Science Association (ERSA), 2005)
This paper develops a unifying framework for spatial and environmental economics, based on equilibrium considerations for population games. The main contribution of this paper consists of introducing a consistent concept for spatial welfare. Following the introduction of estimable locational sorting models for valuation methods in environmental economics, the relationship between the theoretical underpinnings of the hedonic pricing model and the bid rent concept in urban economics is re-examined. This is done along the definition of the ideal general equilibrium willingness to pay (GE-WTP) that is at the heart of most applications of locational sorting models in environmental economics. A GE-WTP should be able to account for the value of non-marginal changes in a spatially explicit distribution of local public goods. Commonly, such a GE-WTP is derived as a Hicksian WTP adjusted for endogenous prices. Endogenous prices are typically enforced by a market clearing condition, often a fixed supply, constraining the relocation of a population in response to the changes in local quality. This paper offers an alternative interpretation of a GE-WTP. It demonstrates how for a discrete choice formulation, a fixed supply generically results in a Nash equilibrium in a population game. Furthermore, it is shown that this Nash equilibrium corresponds exactly to a spatial equilibrium in urban economics. This observation allows for a novel spatially explicit approach to the evaluation of land policy options, combining current cost-benefit practice with the optimization of land use. Finally it is shown, how the GE-WTP can be adjusted for developers' decisions, based on the analogy with urban economic models. It allows this spatial welfare measure to be extended with endogenous, instead of fixed, supply. This makes the concept also suitable for comparing the social welfare implications of entirely different land use patterns.
Keywords: 330